The Industrial IoT Control Design of Three Phase Induction Motor using Conventional V/F Method - Angga Wahyu Aditya; Restu Mukti Utomo; Nur Rani Alham; Hilmansyah Hilmansyah (Faculty of Engineering, Universitas Tanjungpura, 2023)
Nowadays, the Internet of Things (IoT) is inseparable from the industrial revolution 4.0 and society 5.0. IoT allows all aspects to be connected at the same time. In industrial processes, the IoT controls the actuator and monitors the behavior system. Industrial IoT (IIoT) connected the Human Machine Interface (HMI) Haiwell C7S with the actuator (Schneider Altivar 12) and the controller (OMRON CP1E-NA20DRA). The communication between the variable speed drive and Haiwell C7S using Modbus protocol is connected with RS485. Schneider Altivar 12 is a variable-speed drive that controls the Induction Motor (IM) rotor speed using the conventional V/F method. The scalar control of IM controls supply frequency and voltage simultaneously. The success parameter of the proposed systems is a rotor speed response and voltage in various supply frequencies. The results show that the 5 Hz supply frequency makes the absolute error of rotor speed response 11.43% for tachometer measurement, 0.67% from VSD data, and 12.67% for rotary encoder measurement. This absolute error will decrease significantly when the supply frequency exceeds 20 Hz, or the rotor speed response exceeds 1200 rpm. The changes in the supply frequency change the voltage's magnitude. The voltage will increase proportionally, along with the increase in supply frequency.